1990
DOI: 10.1002/aja.1001870203
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst implantation in the chinese hamster (Cricetulus griseus)

Abstract: Embryonic development of the Chinese hamster (Cricetulus griseus) was studied from the onset of implantation to the formation of the parietal yolk sac placenta. Implantation began on day 6 of pregnancy, when the embryo became fixed to the uterine luminal epithelium. At this time there was no zona pellucida, and microvilli of the trophoblast and uterine epithelium were closely apposed. Stromal cells immediately adjacent to the implantation chamber began to enlarge and accumulate glycogen. By day 7 the mural tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…In sites from both delayed and normally implanting mouse blastocysts, decidual cells also penetrated the basement membranes of stromal vasculature and were in contact with endothelial cells and contents of the lumen. Similar activity was seen in the rat (Welsh and Enders, 1987) and Chinese hamster (Blankenship et al, 1990) during implantation. Decidual cells lining the stromal vasculature in the rat are eventually replaced by trophoblast (Welsh and Enders, 1987).…”
Section: Discussionsupporting
confidence: 72%
“…In sites from both delayed and normally implanting mouse blastocysts, decidual cells also penetrated the basement membranes of stromal vasculature and were in contact with endothelial cells and contents of the lumen. Similar activity was seen in the rat (Welsh and Enders, 1987) and Chinese hamster (Blankenship et al, 1990) during implantation. Decidual cells lining the stromal vasculature in the rat are eventually replaced by trophoblast (Welsh and Enders, 1987).…”
Section: Discussionsupporting
confidence: 72%
“…In another rodent species, the Chinese hamster, Blankenship et al [21] found that attachment is quite similar to that in the rat with extensive remodelling of microvilli into irregular protrusions of the plasma membrane and Winterhager and Denker [22] also reported flattening and loss of microvilli in the rabbit. Potts and Racey [23] reported loss of apical microvilli and flattening of the apical plasma membrane in bats during early pregnancy such that uterine epithelial and trophoblast membranes ran parallel and Oliveira et al [24] have more recently reported on membrane flattening in bats.…”
Section: The Apical Plasma Membrane In Other Animalsmentioning
confidence: 89%
“…x 55. blast tissue from different species is clearly capable of extracellular matrix catabolism, as indicated by several lines of research (Salomon and Sherman, 1975;Glass et al, 1983;Fisher et al, 1985Fisher et al, ,1989Yagel et al, 1988). The evidence for decidual cell penetration of basement membrane strongly suggests that these cells can also modify this matrix (Schlafie et al, 1985;Blankenship et al, 1990;Blankenship and Given, 1992). Additionally, results of the present study indicate that loss of laminin and type IV collagen in luminal basement membrane was closely correlated with the mesometrial extent of decidual cell development, with basement membrane lost from areas not in contact with trophoblast tissue.…”
Section: Discussionmentioning
confidence: 99%